Mathematical Modeling of Forgetfulness and Memorization of Mathematical Concepts - Ebenezer Bonyah; Larbi, Ernest; Raphael Owusu (International Journal of Mathematics and Mathematics Education (IJMME), 2023)
Memorization and forgetfulness in Mathematics Education have been major issues in most developing countries, including Ghana. This work explored forgetfulness and memorization in the context of the fractional calculus domain using the Mittag-Leffler function. The Sumudu transform was employed to obtain a special solution. The existence and uniqueness of solutions was established using the concept of the fixed-point theory. It is established that fractional order plays a major role in memorization and forgetfulness of mathematical concepts. It is concluded that factors that enhance the teaching and learning of mathematical concepts should be encouraged.